2011
DOI: 10.1073/pnas.1109806108
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative impact of thymic selection on Foxp3 + and Foxp3 subsets of self-peptide/MHC class II-specific CD4 + T cells

Abstract: It is currently thought that T cells with specificity for self-peptide/ MHC (pMHC) ligands are deleted during thymic development, thereby preventing autoimmunity. In the case of CD4 + T cells, what is unclear is the extent to which self-peptide/MHC class II (pMHCII)-specific T cells are deleted or become Foxp3 + regulatory T cells. We addressed this issue by characterizing a natural polyclonal pMHCII-specific CD4 + T-cell population in mice that either lacked or expressed the relevant antigen in a ubiquitous p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
109
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 102 publications
(122 citation statements)
references
References 47 publications
11
109
2
Order By: Relevance
“…This idea is consistent with the relatively low incidence of autoimmunity in the general population; 3% of the human population suffers from some form of autoimmunity (48). Nevertheless, an individual can probably cope with a small number of high-affinity peripheral T cells and still be considered functionally tolerant, allowing negative selection to be less than perfect, which seems to be the case (49,50). Recent computational studies (51) propose that an immune or autoimmune response requires a minimum (quorum) number of antigen-specific T cells.…”
Section: Discussionsupporting
confidence: 72%
“…This idea is consistent with the relatively low incidence of autoimmunity in the general population; 3% of the human population suffers from some form of autoimmunity (48). Nevertheless, an individual can probably cope with a small number of high-affinity peripheral T cells and still be considered functionally tolerant, allowing negative selection to be less than perfect, which seems to be the case (49,50). Recent computational studies (51) propose that an immune or autoimmune response requires a minimum (quorum) number of antigen-specific T cells.…”
Section: Discussionsupporting
confidence: 72%
“…Although these two models represent two physiologically different settings, the data were indistinguishable and therefore combined where noted. 2W- and OVA-reactive T cell populations are rare in naive, antigen-inexperienced mice (Moon et al, 2011), such that in all experiments, T cell enrichment by negative selection was first performed to increase the frequency of multimer-binding T cells during subsequent flow cytometric analysis. Transplantation tolerance was induced with a combination of anti-CD154 and donor splenocyte transfusion (DST) at the time of transplantation.…”
Section: Resultsmentioning
confidence: 99%
“…For these other specificities, resistance to avidity maturation may be epigenetically imprinted, similar to T cell-intrinsic hyporesponsiveness, which makes cells resistant to secondary encounter of antigen (Philip et al, 2017; Schietinger et al, 2012), or may be constrained by regulatory cells distinct from classical Tregs. Studies of T cells in tumor microenvironments that are deemed dysfunctional and of self-specific T cells (Black et al, 2014; Kuball et al, 2009; Malhotra et al, 2016; Moon et al, 2011; Soong et al, 2014; Souders et al, 2007; Wong et al, 2008; Yu et al, 2015) have also revealed that many of these cells are low avidity at the population level, supporting the idea that tolerance, whether spontaneously acquired in the tumor microenvironment or upon self-antigen encounter or, as we show in this study, therapeutically induced by costimulation blockade therapy, may be simultaneously enforced through multiple mechanisms, one of which being the preservation of low-avidity repertoire for the relevant antigen.…”
Section: Discussionmentioning
confidence: 99%
“…These cells, which are termed natural CD4 + Treg cells (nTregs) (reviewed in 225), respond to antigenic stimulation by differentiating into effector Treg cells 226. There are nTreg cells with specificity for both self and foreign antigens, although the ratio of antigen‐specific FoxP3 + to FoxP3 − cells is higher for the former, enabling more stringent control of responses to autoantigens 227. FoxP3 expression can also be induced in FoxP3 − naive CD4 + T cells in the periphery in response to antigenic stimulation in the presence of IL‐2 and TGFβ,228, 229 resulting in the generation of induced (i)Treg cells.…”
Section: Regulatory Cell Populations and Their Relationship To Bnab Imentioning
confidence: 99%